Colistin Resistance Mechanisms in Human Salmonella enterica Strains Isolated by the National Surveillance Enter-Net Italia (2016-2018) - Daniela Fortini; Slawomir Owczarek; Anna Maria Dionisi; Claudia Lucarelli; Sergio Arena; Alessandra Carattoli; Enter-Net Italia Colistin Resistance Study Group; Laura Villa; Aurora García-Fernández (MDPI AG, 2022)
Background: A collection of human-epidemiologically unrelated S. enterica strains collected over a 3-year period (2016 to 2018) in Italy by the national surveillance Enter-Net Italia was analysed. Methods: Antimicrobial susceptibility tests, including the determination of minimal inhibitory concentrations (MICs) for colistin, were performed. Colistin resistant strains were analysed by PCR to detect mobile colistin resistance (mcr) genes. In mcr-negative S. enterica serovar Enteritidis strains, chromosomal mutations potentially involved in colistin resistance were identified by a genomic approach. Results: The prevalence of colistin-resistant S. enterica strains was 7.7%, the majority (87.5%) were S. Enteritidis. mcr genes were identified only in one strain, a S. Typhimurium monophasic variant, positive for both mcr-1.1 and mcr-5.1 genes in an IncHI2 ST4 plasmid. Several chromosomal mutations were identified in the colistin-resistant mcr-negative S. Enteritidis strains in proteins involved in lipopolysaccharide and outer membrane synthesis and modification (RfbN, LolB, ZraR) and in a component of a multidrug efflux pump (MdsC). These mutated proteins were defined as possible candidates for colistin resistance in mcr-negative S. Enteritidis of our collection. Conclusions: The colistin national surveillance in Salmonella spp. in humans, implemented with genomic-based surveillance, permitted to monitor colistin resistance, determining the prevalence of mcr determinants and the study of new candidate mechanisms for colistin resistance.